Peran Account Officer Dalam Penentuan Pengajuan Pembiayaan Di Bank Sumut Syariah KC Medan Katamso - Subandi, Subandi; Atika, Atika (LPPM Universitas Labuhanbatu, 2023)
This research was conducted at Bank Sumut Syariah Medan KC Medan Katamso. The purpose of this study is to explain how the role and strategy implemented by Account officers in determining the feasibility of applying for financing at Bank Sumut Syariah Medan KC Medan Katamso and to explain the supporting & inhibiting factors for Account officers in determining the feasibility of applying for financing at Bank Sumut Syariah Medan KC Medan Katamso as well as explaining the solution of the problematic inhibiting factors. The methodology used in this research is qualitative with interview and observation data collection techniques. The results of this study indicate that the strategy implemented by account officers in determining the eligibility of applying for financing at the Medan KC Medan Katamso Sumut Syariah Bank is adjusted by conducting a survey first to customers. Then it is determined by applying the 5C principle. The inhibiting factors faced by Account officers in determining the feasibility of filing financing are the lack of information on customers, misuse of proposed financing, incomplete customer data. The solution is to re-analyze the 5C principles, and be able to take advantage of current technology, for example customers don't have to bother delivering documents to the bank, customers can use camscanner or pdf to submit documents online to the bank.